Chasing the offshore wind farm wind-wake-induced upwelling/downwelling dipole - Floeter, Jens; Pohlmann, Thomas; Harmer, André; Möllmann, Christian (Frontiers in Marine Science, 2022)
The operational principle of Offshore Wind Farms (OWF) is to extract kinetic energy from the atmosphere and convert it into electricity. Consequently, a region of reduced wind speed in the shadow zone of an OWF, the so-called wind-wake, is generated. As there is a horizontal wind speed deficit between the wind-wake and the undisturbed neighboring regions, the locally reduced surface stress results in an adjusted Ekman transport. Subsequently, the creation of a dipole pattern in sea surface elevation induces corresponding anomalies in the vertical water velocities. The dynamics of these OWF wind-wake induced upwelling/downwelling dipoles have been analysed in earlier model studies and strong impacts on stratified pelagic ecosystem have been predicted. Here we provide for the first-time empirical evidence of the existence of such upwelling/downwelling dipoles. The data were obtained by towing a remotely operated vehicle (TRIAXUS ROTV) through leeward regions of operational OWFs in the summer stratified North Sea. The undulating TRIAXUS transects provided high-resolution CTD data which enabled the characterisation of three different phases of the ephemeral life-cycle of a wind-wake induced upwelling/downwelling dipole: development, operation and erosion. We identified two characteristic hydrographic signatures of OWF-induced dipoles: distinct changes in mixed layer depth and potential energy anomaly over a distance < 5 km and a diagonal excursion of the thermocline of 10-14 m over a dipole dimension of 10-12 km. Whether these anthropogenically induced abrupt changes are significantly different from the corridor of natual variability awaits further investigations.